The control of the discrimination between dNTP and rNTP in DNA and RNA polymerase - Yoon, Hanwool (Proteins, 2016)
Understanding the origin of discrimination between rNTP and dNTP by DNA/RNA polymerases is important both for gaining fundamental knowledge on the corresponding systems and for advancing the design of specific drugs. This work explores the nature of this discrimination by systematic calculations of the transition state (TS) binding energy in RB69 DNA polymerase (gp43) and T7 RNA polymerase. The calculations reproduced the observed trend, in particular when they included the water contribution obtained by the water flooding approach. Our detailed study confirms the idea that the discrimination is due to the steric interaction between the 2′OH and Tyr416 in DNA polymerase, while the electrostatic interaction is the source of the discrimination in RNA polymerase.